Relevansi Adat Istiadat Gayo Lues dalam Konteks Perubahan Sosial: Perspektif Generasi Muda - Darmawan, Wahyu; Radiansyah, Radiansyah (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: The aim of this study is to analyze the phenomenon of the relevance of the traditional customs of the Gayo Lues Tribe in the context of social change from the perspective of the younger generation. Within a sociological framework, these customs are interpreted as obligations that serve as a significant foundation in the decision-making process to resolve social issues. This research utilizes a qualitative method, with a literature review approach. The data collected through this process is then analyzed descriptively, analytically, historically, and comparatively. The findings reveal a gap in the younger generation's understanding of the traditional customs of the Gayo tribe in Aceh. Despite this, the younger generation plays a vital role in preserving cultural identity and the continuity of traditional customs and requires preventive assimilation. Furthermore, the renewal and adaptation of customs are necessary for the younger generation to maintain their relevance in a modern context. The research also explores contemporary challenges in the changes in values and norms experienced by the younger generation, which potentially threaten the relevance of traditional customs. The implications of the research involve establishing a dialogue to reach a consensus among the younger generation, the older generation, and traditional leaders.   Abstrak: Penelitian ini bertujuan untuk menganalisis fenomena relevansi adat istiadat Suku Gayo Lues dalam konteks perubahan sosial perspektif generasi muda. Dalam kerangka sosiologis, adat istiadat diinterpretasikan sebagai kewajiban yang menjadi landasan penting dalam proses pengambilan keputusan untuk menyelesaikan masalah sosial. Penelitian ini menggunakan metode kualitatif, dengan pendekatan penelitian kepustakaan. Data yang dikumpulkan melalui proses ini kemudian dianalisis secara deskriptif, analitis, historis, dan komparatif. Hasil penelitian mengungkap kesenjangan pemahaman adat istiada pada generasi muda Suku Gayo di Aceh. Meski demikian generasi muda berperan penting dalam mempertahankan identitas budaya dan kesinambungan adat istiadat dan membutuhkan asimilasi preventif. Selain itu diperlukan pembaharuan dan adaptasi adat istiadat, generasi muda dapat menjaga relevansinya dalam konteks modern. Penelitian juga mengeksplorasi tantangan kontemporer pada perubahan nilai dan norma yang dialami oleh generasi muda, yang berpotensi mengancam relevansi adat istiadat. Penelitian berimplikasi membentuk dialog untuk mencapai konsensus antara generasi muda, generasi yang lebih tua, dan tokoh adat.